DEVELOPMENT OF MAGNETIC RESONANCE IMAGING (MRI) TECHNIQUES FOR STUDYING NEUROLOGICAL CHANGES ASSOCIATED WITH BRAIN DISEASES - Abdalrahman Ahmed Yassen Mahmoud; Marwan Khaled Ibrahim Ahmed; Teba Haitham Jameel Mohammed; Athraa Mahmoud Mohamed Hani; Halah madhor Mahmoud (Journal of Medical Genetics and Clinical Biology, 2024)
General Background: The advent of advanced Magnetic Resonance Imaging (MRI) techniques has transformed the exploration of neurological alterations linked to brain diseases. Specific Background: MRI serves as a non-invasive modality for visualizing brain structure and function, crucial for identifying abnormalities associated with conditions such as Alzheimer's disease, Parkinson's disease, multiple sclerosis, and stroke. Knowledge Gap: Despite the advancements, the precise relationships between these imaging modalities and specific neurological changes remain inadequately understood, necessitating further investigation. Aims: This review aims to examine the latest developments in MRI techniques, particularly functional MRI (fMRI), diffusion tensor imaging (DTI), and magnetic resonance spectroscopy (MRS), and their applications in assessing neurological disorders. Results: The integration of fMRI facilitates the capture of real-time brain activity through blood oxygen level-dependent (BOLD) signals, while DTI provides insights into white matter integrity and neural connectivity. MRS enhances our understanding of biochemical alterations by measuring metabolic changes within the brain. Novelty: This synthesis of advanced MRI methodologies underscores their complementary roles in elucidating the intricacies of brain structure and function, particularly in the context of disease progression and treatment response. Implications: By delineating subtle changes in brain activity and composition, these MRI techniques not only enhance early diagnosis but also inform clinical strategies for the management of brain diseases, ultimately contributing to improved patient outcomes. This review highlights the potential of advanced MRI modalities in bridging existing knowledge gaps and advancing both research and clinical practices in neurology.